Incidence and cost of sexual violence in Iowa - Yang, J.; Miller, Ted; Zhang, N.; Lehew, B.; Peek-Asa, C. (Elsevier Inc., 2014)
Background Sexual violence is a serious and costly public health problem. Current research that systematically documents the broad range of economic costs of sexual violence is lacking. Purpose To estimate the incidence and costs of sexual violence in Iowa in 2009. Methods Using data obtained from population surveys, six Iowa government agencies, and other sources, we estimated sexual violence incidence, costs per incident, and total costs in 2009 dollars, by age and sexual violence category, and for various cost elements. We calculated direct costs of medical care, mental health care, property damage, victim services, investigation, adjudication, and sanctioning, as well as indirect costs for lost work and quality of life. We collected data in 2010-2011 and completed analysis in 2013. Results In 2009, an estimated 55,340 individuals experienced sexual violence in Iowa, including 49,510 adults and 5,930 children. Nearly three of every four victims were women. The estimated total cost of sexual violence in 2009 was $4.7 billion, equating to $1,580 per resident. This estimate included $4.44 billion in indirect costs and $265 million in direct costs. In the same year, the government spent an estimated $100.6 million as a result of sexual violence in Iowa, more than half of which ($55.3 million) was spent on perpetrators and little ($0.9 million) on prevention. Conclusions The economic costs of sexual violence are high for individuals and society. Cost information can help identify the burden of sexual violence relative to other social problems in Iowa and prioritize funding for prevention and intervention. © 2014 American Journal of Preventive Medicine.